检测肿瘤复发的方法 (2023)
本发明涉及用于检测肿瘤复发的对象特异性方法，该方法以对该对象的肿瘤的克隆/亚克隆突变图谱的认识以及在其无细胞DNA（cfDNA）中的突变的检测为基础，通常通过多重PCR检测肿瘤突变（例如单核苷酸变异（SNV））。 The invention relates to subject-specific methods for detecting recurrence of tumours based on an understanding of the clonal/subclonal mutation profile of the subject's tumour and detection of the mutations in their cell-free DNA (cfDNA), typically by multiplex PCR of tumour mutations such as single nucleotide variants (SNVs).